C57Bl/6N mice have an attenuated lung inflammatory response to dsRNA compared to C57Bl/6J and BALB/c mice - Sofia Malm Tillgren; Juan José Nieto-Fontarigo; Samuel Cerps; Sangeetha Ramu; Mandy Menzel; Irma Mahmutovic Persson; Anja Meissner; Hamid Akbarshahi; Lena Uller (Journal of Inflammation, 2023)
Abstract Background Lower respiratory infections caused by ssRNA viruses are a major health burden globally. Translational mouse models are a valuable tool for medical research, including research on respiratory viral infections. In in vivo mouse models, synthetic dsRNA can be used as a surrogate for ssRNA virus replication. However, studies investigating how genetic background of mice impacts the murine lung inflammatory response to dsRNA is lacking. Hence, we have compared lung immunological responses of BALB/c, C57Bl/6N and C57Bl/6J mice to synthetic dsRNA. Methods dsRNA was administered intranasally to BALB/c, C57Bl/6N and C57Bl/6J mice once/day for three consecutive days. Lactate dehydrogenase (LDH) activity, inflammatory cells, and total protein concentration were analyzed in bronchoalveolar lavage fluid (BALF). Pattern recognition receptors levels (TLR3, MDA5 and RIG-I) were measured in lung homogenates using RT-qPCR and western blot. Gene expression of IFN-β, TNF-α, IL-1β and CXCL1 was assessed in lung homogenates by RT-qPCR. ELISA was used to analyze protein concentrations of CXCL1 and IL-1β in BALF and lung homogenates. Results BALB/c and C57Bl/6J mice showed infiltration of neutrophils to the lung, and an increase in total protein concentration and LDH activity in response to dsRNA administration. Only modest increases in these parameters were observed for C57Bl/6N mice. Similarly, dsRNA administration evoked an upregulation of MDA5 and RIG-I gene and protein expression in BALB/c and C57Bl/6J, but not C57Bl/6N, mice. Further, dsRNA provoked an increase in gene expression of TNF-α in BALB/c and C57Bl/6J mice, IL-1β only in C57Bl/6N mice and CXCL1 exclusively in BALB/c mice. BALF levels of CXCL1 and IL-1β were increased in BALB/c and C57Bl/6J mice in response to dsRNA, whereas the response of C57Bl/6N was blunt. Overall, inter-strain comparisons of the lung reactivity to dsRNA revealed that BALB/c, followed by C57Bl/6J, had the most pronounced respiratory inflammatory responses, while the responses of C57Bl/6N mice were attenuated. Conclusions We report clear differences of the lung innate inflammatory response to dsRNA between BALB/c, C57Bl/6J and C57Bl/6N mice. Of particular note, the highlighted differences in the inflammatory response of C57Bl/6J and C57Bl/6N substrains underscore the value of strain selection in mouse models of respiratory viral infections.